The tension between naturalness and accuracy in translating lexical collocations in literary text - Obeidat, Adham Mousa; Ayyad, Ghada Rajeh; Tengku Sepora Tengku Mahadi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this study is to find out the errors that may be resulted when translating lexical collocations due to the translators’ tension between naturalness and accuracy when translating literary texts from Arabic into English. The study adopts the analytical descriptive qualitative research design which concludes that the translators may produce three types of errors due to the tension between naturalness and accuracy, which are: natural – inaccurate, unnatural – accurate, and unnatural – inaccurate. The results show that the two translators commit 24 errors due to this tension, and that the errors of having natural- inaccurate translation consist most of the total errors found. The study concludes that translator should pay more attention to the concepts of naturalness and accuracy when dealing with collocations. Otherwise, the translated collocation will be either unnatural and being odd for the target text readers or causing a meaning loss or distortion. The scientific novelty of the present study lies in discussing the problem of tension between naturalness and accuracy when translating lexical signs in the form of collocations. Findings of the study have pedagogical implications for translators in general, translators of literature, translation students, and teachers. Findings of the lexical analysis of collocations also presents an essential resource for researchers of lexical and semantic studies to translate between Arabic and English.